2001
DOI: 10.1264/jsme2.2001.227
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in Temperature Dependence of Methane Production in Paddy Soil.

Abstract: Changes in methanogenic activity were determined in slurries of soil collected from a paddy field. Acetate or H 2 added as a methanogenic substrate stimulated methane production in most samples. In soil collected when the field was continuously flooded, the two substrates affected production similarly, while in the samples collected when the field had been drained, H 2 stimulated production more strongly than acetate. The effect of temperature on methane production in paddy soil was also investigated. In conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…Rice straw had been applied annually to this plot for more than 20 years. Cultivation practices for rice plants and characteristics of the soil were described previously (Ueki et al, 1999Kaku et al, 2000;Hattori et al, 2001Hattori et al, , 2002. Strains were isolated by selecting individual colonies after counting anaerobic bacteria on plant residue collected from the soil.…”
Section: Methodsmentioning
confidence: 99%
“…Rice straw had been applied annually to this plot for more than 20 years. Cultivation practices for rice plants and characteristics of the soil were described previously (Ueki et al, 1999Kaku et al, 2000;Hattori et al, 2001Hattori et al, , 2002. Strains were isolated by selecting individual colonies after counting anaerobic bacteria on plant residue collected from the soil.…”
Section: Methodsmentioning
confidence: 99%
“…Wassman et al [156] observed a faster development of CH 4 production rate and higher maximum value with increasing temperatures between 25 and 35°C. Hattori et al [59] recorded optimum temperature of 40°C for CH 4 production in Japanies paddy fields due to dominance of methanogenic population at this temperature.…”
Section: Temperaturementioning
confidence: 98%
“…The biogenic methane is mostly produced by methanogenic archaea (methanogens) in anaerobic environments i.e. sediments and flooded rice fields [59]. Each year methanogens produce about 400 million metric tons of CH 4 [49].…”
Section: Introductionmentioning
confidence: 99%
“…If the supply of substrates in the slurry is limited. the methanogenic rate during the incubation should also be limited (Hattori et al 2001).I To whom correspondence should be addressed.Therefore. the effects of the addition of methanogenic substrates, that is, acetate or H 2 • on the methanogenic rates of paddy soil slurries were examined in this investigation and vertical and seasonal changes in the methanogenic activity were monitored for :2 years.…”
mentioning
confidence: 99%
“…H 2 0 and autoclaved) was added to each soil sample (1 : I) and the soil slurry was put into tubes (18 mm in diameter X 180 mm in height) under the N2 gas flow. Each tube containing 10 mL of slurry was sealed under the gas flow with a butyl-rubber double stopper and immediately incubated at 30'C for 8 h. For the determination of the methanogenic activity with the addition of substrates, sodium acetate was introduced into the slurry at a final concentration of 10 mM or N2 gas in each tube was replaced with H2 gas (Hattori et al 2001). The concentration of methane in the headspace of the tubes was measured at intervals of 2 h by gaschromatography (263 or G-5000 gas-chromatograph, Hitachi.…”
mentioning
confidence: 99%